Asna1/TRC40-mediated membrane insertion of tail-anchored proteins - Favaloro, Vincenzo; Vilardi, Fabio; Schlecht, Rainer; Mayer, Matthias P.; Dobberstein, Bernhard (Journal of cell science, 2010)
Tail-anchored (TA) proteins insert post-translationally into the membrane of the endoplasmic reticulum (ER) and span the membrane by their C-terminal transmembrane domain. We have reconstituted membrane insertion of TA proteins from recombinant Asna1/TA protein complexes and ER-derived membranes. Our data show that Asna1 can mediate membrane insertion of RAMP4 and Sec61β without the participation of other cytosolic proteins by a mechanism that depends on the presence of ATP or ADP and a protease-sensitive receptor in the ER membrane. By contrast, membrane insertion of cytochrome b5 can proceed independently of Asna1 and nucleotides.
Gesehen am 13.02.2023